Clinical and Neuropathogenetic Aspects of Human African Trypanosomiasis - Kennedy, Peter G. E.; Rodgers, Jean (Frontiers in Immunology, 2019)
Trypanosomiasis has been recognised as a scourge in sub-Saharan Africa for centuries. The disease, caused by protozoan parasites of the Trypanosoma genus, is a major cause of mortality and morbidity in animals and man. Human African trypanosomiasis (HAT), or sleeping sickness, results from infections with T. brucei (b.) gambiense or T. b. rhodesiense with T. b. gambiense accounting for over 95% of infections. Historically there have been major epidemics of the infection, followed by periods of relative disease control. As a result of concerted disease surveillance and treatment programmes, implemented over the last two decades, there has been a significant reduction in the number of cases of human disease reported. However the recent identification of asymptomatic disease carrier gives cause for some concern. The parasites evade the host immune system by switching their surface coat, comprised of variable surface glycoprotein (VSG). In addition, they have evolved a variety of strategies, including the production of serum resistance associated protein (SRA) and T. b. gambiense-specific glycoprotein (TgsGP) to counter host defence molecules. Infection with either disease variant results in an early haemolymphatic-stage followed by a late encephalitic-stage when the parasites migrate into the CNS. The clinical features of HAT are diverse and non-specific with early-stage symptoms common to several infections endemic within sub-Saharan Africa which may result in a delayed or mistaken diagnosis. Migration of the parasites into the CNS marks the onset of late-stage disease. Diverse neurological manifestations can develop accompanied by a neuroinflammatory response, comprised of astrocyte activation and inflammatory cell infiltration. However, the transition between the early and late-stage is insidious and accurate disease staging, although crucial to optimise chemotherapy, remains problematic with neurological symptoms and neuroinflammatory changes recorded in early-stage infections. Further research is required to develop better diagnostic and staging techniques as well as safer more efficacious drug regimens. Clearer information is also required concerning disease pathogenesis, specifically regarding asymptomatic carriers and the mechanisms employed by the trypanosomes to facilitate progression to the CNS and precipitate late-stage disease. Without progress in these areas it may prove difficult to maintain current control over this historically episodic disease.